Faktor-faktor yang Mempengaruhi Intensi Pelanggan dalam Menggunakan Online Food Delivery (OFD) di Indonesia - Soemitro, Fadhillah; Perkasa, Muhammad Ichsan; Arifin, Nathaniel Marvel; Wulansari, Safitri; Julia, Tiffany (Universitas Bunda Mulia, 2023)
The rapid development of the Internet and technology had a big impact on the usage of online shopping including online food delivery (OFD) services. What factors affect the customer's intention on using online food delivery (OFD)? This study aims to investigate the factors affecting customer intention (CIU) on using online food delivery (OFD) services in Indonesia. This study used an online survey for data collection by distributing online questionnaires (57 questions) to OFD users in Indonesia. Factor analysis resulted in 11 variables and the multiple regression analysis was used to examine the impacts of 10 variables on CIU. Regression analysis results proved that Visibility, Perceived Usefulness, Time Saving Benefit, and Price Saving Benefit had positive and significant effects on customer intention to use OFD. This study focuses on Indonesia’s OFD services, so the findings may not be applicable in other cultural contexts. This limited generalizability can be addressed by future researchers trying to validate the findings of this study in other cultural backgrounds and geographies. In terms of dimension, the ten constructs might not be the only factors that affect CIU. Hence, examining underexplored dimensions on CIU is also needed.